Effect of Product Quality, Brand Image And Life Style Against Buying Decision - Tubagus Ahmad Darojat (Institute of Computer Science (IOCS), 2020)
The research aims to analyze the effect of product quality, brand image and life style on consumer purchasing decisions at Metropolitan Mall Bekasi. The sample used in this study was 98 respondents clothing stores in Metropolitan Mall Bekasi. Probability sampling with accidental sampling approach is used as a sampling technique. Quantitative research methods with multiple linear regression analysis using SPSS analysis tool version 20.0. The results of this study indicate that product quality has a positive and significant effect on consumer purchasing decisions at Metropolitan Mall Bekasi. Brand image has a positive and significant influence on consumer purchasing decisions at Metropolitan Mall Bekasi. Life style has a negative and no significant influence on consumer purchasing decisions in Metropolitan Mall Bekasi. Product quality, brand image and life style have a positive and significant influence on consumer purchasing decisions at Metropolitan Mall Bekasi.